Viewing animal migration through a social lens. (November 2022) - Aikens, Ellen O.; Bontekoe, Iris D.; Blumenstiel, Lara; Schlicksupp, Anna; Flack, Andrea
Abstract : Evidence of social learning is growing across the animal kingdom. Researchers have long hypothesized that social interactions play a key role in many animal migrations, but strong empirical support is scarce except in a few unique systems and species. In this review, we aim to catalyze advances in the study of social migrations by synthesizing research across disciplines and providing a framework for understanding when, how, and why social influences shape the decisions animals make during migration. Integrating research across the fields of social learning and migration ecology will advance our understanding of the complex behavioral phenomena of animal migration and help to inform conservation of animal migrations in a changing world. Highlights: Social influences (i.e., social information use, social learning, and culture) are often assumed to play a role in animal migration, but studying social aspects of migration remains a challenge. We evaluate support for predictions from the social learning literature within the context of migration, and suggest that social influences during migration are likely more widespread than previously recognized. To study social migration, future research can leverage next-generation tracking techniques and experimental manipulations of the social environment. Movement diversity constitutes the building blocks of migration culture, and thus warrants further consideration in conservation and management of migratory species.